ANALISA KEPUASAN KINERJA CLEANING SERVICE (Studi Kasus : PT. ARTHA KEMBAR UTAMA di UIN SUNAN AMPEL SURABAYA) - Aldi Bayu Wicaksono (AGROTERAP : Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2023)
PT. ARTHA KEMBAR UTAMA is a well – known cleaning service provider company in the province at East Java. A service company located at Puri Surya Jaya Housing Cluster Taman Nagoya, blk E2 – E4 No. 45, Sidoarjo Regency, East Java, is often trusted in handling cleaning matters.many agencies have been entrusted to this company, starting from Airlangga University Hospital, Hospital in Madiun Regency, and Ofcourse the place that I will use as research for this project, namely Sunan Ampel State Islamic University, Surabaya. Consumer satisfaction greatly influeces the assessment of the quality of a cleaners work, therefore it is important for every company to conduct a test or assessment of consumer/user satisfaction. To find out the level of consumer satisfaction with food, a comparison was made of the level exizting satisfaction and satisfaction after the research.